RADIONUCLIDE STUDIES IN PEDIATRIC PRACTICE: INTERACTION OF RESEARCHER, CHILD AND PARENTS - D.K. Fomin; S.P. Yatsyk; E.V. Yatsyk; O.A. Borisova; A.A. Nazarov (Union of pediatricians of Russia, 2007)
The authors consider the issues interaction between a doctor and a child during the radionuclide study. They also give recommendations of the pediatric council under auspices of the European society of the nuclear medicine to carry on the scintigraphic studies among the children. The article high lights the basic moments as to the psychoprophylactic preparation of the children for the radionuclide study with regard to their age and character peculiarities. The researchers offer approaches to define the psychic and emotional status of the child, degree of anxiety before the study and methods to eliminate it, allowing for considerable quality improvement of the performed procedure.Key words: children, radionuclide diagnostics, pediatric radiology, psychoprophylactic preparation.